PENGARUH INSENTIF PAJAK, KUALITAS PELAYANAN FISKUS, DAN SISTEM SELF ASSESMENT TERHADAP KEPATUHAN WAJIB PAJAK DENGAN SOSIALISASI PAJAK SEBAGAI VARIABEL MODERASI - Yoga Radyasa; Waluyo (Jurnal Kontemporer Akuntansi, 2025)
This research is a significant step in understanding the dynamics of taxpayer compliance among MSMEs registered with KPP Pratama Jakarta. Involving the variables Tax Incentives, Fiscus Service Quality, and Self Assessment System as predictors, as well as Tax Socialization as a moderating factor, this research uses multiple linear regression analysis methods. The results are interesting, showing that Tax Incentives have a significant positive impact on the level of taxpayer compliance. On the other hand, Fiscus Service Quality and the Self Assessment System have a negative impact, indicating the complexity of the factors involved in encouraging tax compliance. The role of Tax Socialization as a moderating factor provides further insight. This factor strengthens the positive impact of Tax Incentives and Service Quality, while at the same time moderating the negative impact of the Self Assessment System. These results not only show the complexity of the relationships between variables, but also highlight the importance of tax education in increasing taxpayer compliance among MSMEs. These findings provide a valuable contribution to theoretical and applied understanding in the context of tax studies.